The joint Rouse-Zimm theory of the dynamics of polymers in dilute solutions - Lisy, V.; Tothova, J.; Zatovsky, A. (Condensed Matter Physics, 2006)
We propose a theory of the dynamics of polymers in dilute solution, in which the popular Zimm and Rouse models are just the limiting cases of an infinitely large and small draining parameter. The equation of motion for the polymer segments (beads) is solved together with Brinkman’s equation for the solvent velocity that takes into account the presence of other polymer coils in the solution. The equation for the polymer normal modes is obtained and the relevant time correlation functions are found. A tendency to the time-dependent hydrodynamic screening is demonstrated on the diffusion of the polymers as well as on the relaxation of their internal modes. With the growing concentration of the coils in the solution, they both show a transition to the exactly Rouse behaviour. The shear viscosity of the solution, the Huggins coefficient and other quantities are calculated and shown to be notably different from the known results.